Fine Structure of the Breakthrough Phase of the Attachment Process in a Natural Lightning Flash. Issue 6 (19th March 2021) - Jiang, Rubin; Srivastava, Abhay; Qie, Xiushu; Yuan, Shanfeng; Zhang, Hongbo; Sun, Zhuling; Wang, Dongfang; Wang, Caixia; Lv, Guanlin; Li, Zongxiang
Abstract: A lightning flash striking a 325‐m tower was captured using a high‐speed camera operated at 380 kfps and the characteristics of breakthrough phase (BTP) were recorded in two consecutive frames. The fine time‐resolved images indicate that the common streamer zone (CSZ) formed when the bright tips of negative and positive leaders were ≥23 m apart from each other. During BTP, both the negative and positive leaders extended their channels with enhanced luminosity and the gap between them was shortened to 16 m in the frame prior to return stroke. A space leader‐like luminous segment was found within the route of leader connection. This route is inferred to have already been determined at the initial formation of CSZ, by the interconnected streamers of approaching leaders. The dominant growth of this route is interpreted as a new scenario for the conversion of a high‐impedance CSZ to a hot plasma channel during BTP. Plain Language Summary: The breakthrough phase in the attachment process of a cloud‐to‐ground lightning flash occurs when the approaching downward leaders collide with the responding upward connecting leader of the opposite polarity. The breakthrough phase converts the gap between the downward leader and the ground from non‐conducting free air to a high‐impedance common streamer zone and then to a hot plasma channel. Because the breakthrough phase determines which object on the ground is struck by the lightning flash, it is important in both lightning physics and lightning protection. Here we present new findings about the physical characteristics of the breakthrough phase based on comprehensive observations of the electric field changes and a high‐speed optical video, which captured for the first time two clear, consecutive images of the formation of common streamer zones in natural lightning. These results improve our understanding of lightning disasters by providing new insights into the generation of return stroke and can be used to support the modification and improvement of lightning models. Key Points: Two consecutive images showing the breakthrough phase of the attachment process in natural lightning were captured for the first time Weak luminous route appeared, linking the heads of negative and positive leaders, accompanied by the slow front in E‐field of return stroke A space stem/leader‐like luminous segment was observed inside the common streamer zone just before the return stroke frame